The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/ajt.15116
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional transfer of Anelloviridae lineages between graft and host during lung transplantation

Abstract: Solid organ transplantation disrupts virus-host relationships, potentially resulting in viral transfer from donor to recipient, reactivation of latent viruses, and new viral infections. Viral transfer, colonization, and reactivation are typically monitored using assays for specific viruses, leaving the behavior of full viral populations (the "virome") understudied. Here we sought to investigate the temporal behavior of viruses from donor lungs and transplant recipients comprehensively. We interrogated the bron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 56 publications
2
42
0
Order By: Relevance
“…The output sam files were process by Samtools 43 , Bedtools 44 and custom code ( https://github.com/guanxiangliang/liang2019 ) to quantify the fraction of the genome covered. We favor use of percent coverage as a metric for genome detection 45 ; amplification during sequence library preparation can yield many copies of single genome regions, yielding many sequence reads but with low genome coverage. Comparisons in several studies thus indicate coverage is a more reliable measure.…”
Section: Methodsmentioning
confidence: 99%
“…The output sam files were process by Samtools 43 , Bedtools 44 and custom code ( https://github.com/guanxiangliang/liang2019 ) to quantify the fraction of the genome covered. We favor use of percent coverage as a metric for genome detection 45 ; amplification during sequence library preparation can yield many copies of single genome regions, yielding many sequence reads but with low genome coverage. Comparisons in several studies thus indicate coverage is a more reliable measure.…”
Section: Methodsmentioning
confidence: 99%
“…Additional eukaryotic viruses frequently detected include Adenoviridae , Herpesviridae and Papillomaviridae 29 , 58 62 . Phages are commonly found, including Caudovirales , Microviridae and Inoviridae 29 , 58 62 . Phages, like most of the cellular microbiota, even when found in the lung appear to be derived mainly from the abundant bacterial populations in the mouth and upper respiratory tract.…”
Section: Virome Of Different Body Sitesmentioning
confidence: 99%
“…on respiratory tract samples including sputum, naso pharyngeal swabs and bronchoalveolar lavage, showing that the healthy human lung and respiratory tract can be populated by large viral communities 29,[58][59][60][61][62] . Among human DNA viruses, Anelloviridae has been reported to be the most prevalent family of DNA viruses, followed by Redondoviridae 32 .…”
Section: Respiratory Tract Virome Analyses Have Been Performedmentioning
confidence: 99%
“…While attempting to study human virome in bronchoalveolar lavage (BAL) samples of lung transplant patients [ 1 , 2 ], Abbas and colleagues identified sequence reads that aligned with low-coverage to a poorly characterized circovirus, named porcine stool-associated circular virus-5 (PoSCV-5) [ 3 ]. Further genomic characterization of these reads revealed that they belonged to a novel virus having a single, closed molecule of circular DNA approximately 3000 nucleotides (nt) in length called Redondovirus (ReDoV) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%